Attitudes and knowledge of Malaysian extension agents regarding sustainable agriculture - Tiraieyari, Neda; Hamzah, Azimi; Abu Samah, Bahaman; Uli, Jegak (Universiti Putra Malaysia, 2012)
In general, sustainable agriculture instructs farmers to reduce their use of chemicals on the land. Extension agents play a key role in helping farmers in their decision-making processes regarding the environment. The Department of Agriculture has earmarked sustainable agricultural practices (SAP) to transfer unsustainable agriculture into a sustainable manner. The SAP should be transferred by extension agents to the farmers. However little is known about Malaysian extension agents’ attitudes and knowledge towards SAP. A total of 400 front line extension agents in the DOA were surveyed to identify their attitudes and knowledge on SAP. A descriptive research design was used to collect data from extension agents. Results revealed that extension agents’ attitudes and knowledge on SAP are in favor. It is recommended to find out to what extent extension agents attitudes and knowledge has played significant role to transfer SAP to the farmers.